Industrial Acetogenic Biocatalysts: A Comparative Metabolic and Genomic Analysis - Bengelsdorf, Frank R.; Poehlein, Anja; Linder, Sonja; Erz, Catarina; Hummel, Tim; Hoffmeister, Sabrina; Daniel, Rolf; Dürre, Peter (Frontiers in Microbiology, 2016)
Synthesis gas (syngas) fermentation by anaerobic acetogenic bacteria employing the Wood-Ljungdahl pathway is a bioprocess for production of biofuels and biocommodities. The major fermentation products of the most relevant biocatalytic strains (Clostridium ljungdahlii, C. autoethanogenum, C. ragsdalei, and C. coskatii) are acetic acid and ethanol. A comparative metabolic and genomic analysis using the mentioned biocatalysts might offer targets for metabolic engineering and thus improve the production of compounds apart from ethanol. Autotrophic growth and product formation of the four wild type (WT) strains were compared in uncontrolled batch experiments. The genomes of C. ragsdalei and C. coskatii were sequenced and the genome sequences of all four biocatalytic strains analyzed in comparative manner. Growth and product spectra (acetate, ethanol, 2,3-butanediol) of C. autoethanogenum, C. ljungdahlii, and C. ragsdalei were rather similar. In contrast, C. coskatii produced significantly less ethanol and its genome sequence lacks two genes encoding aldehyde:ferredoxin oxidoreductases (AOR). Comparative genome sequence analysis of the four WT strains revealed high average nucleotide identity (ANI) of C. ljungdahlii and C. autoethanogenum (99.3%) and C. coskatii (98.3%). In contrast, C. ljungdahlii WT and C. ragsdalei WT showed an ANI-based similarity of only 95.8%. Additionally, recombinant C. ljungdahlii strains were constructed that harbor an artificial acetone synthesis operon (ASO) consisting of the following genes: adc, ctfA, ctfB, and thlA (encoding acetoacetate decarboxylase, acetoacetyl-CoA:acetate/ butyrate:CoA-transferase subunits A and B, and thiolase) under the control of thlA promoter (PthlA) from C. acetobutylicum or native pta-ack promoter (Ppta-ack) from C. ljungdahlii. Respective recombinant strains produced 2-propanol rather than acetone, due to the presence of a NADPH-dependent primary-secondary alcohol dehydrogenase that converts acetone to 2-propanol. Furthermore, the ClosTronTM system was used to construct an adhE1 integration mutant. These results provide extensive insights into genetic features of industrially relevant bacterial biocatalysts and expand the toolbox for metabolic engineering of acetogenic bacteria able to ferment syngas.